Energy Plantations in India-prospects and Perspectives - Oka, A. G. (Indian Forester, 1981)
The threatening energy crisis coupled with increased energy requirement for expanding population necessitates immediate planning for energy from biomass. In a traditiona1 country like India drastic steps to revolutionise fuelwood production is called for. This paper outlines the projected estimate of fuelwood, land required to grow fuelwood, possible sources of land that could be tapped for fuelwood and management of various types of areas for fuelwood. Research requirement on silvicultural and economic aspects is also emphasized.